plzz answer fast
tan3x.tan2x.tanx = tan3x-tan2x-tanx
Answers
Answered by
2
tan3x=tan(2x+x)
tan 3x = tan2x+tanx/1-tan2xtanx
tan3x-tanxtan2xtan3x=tan2x+tanx
tan3x-tan2x-tanx=tan3xtan2xtanx
tan 3x = tan2x+tanx/1-tan2xtanx
tan3x-tanxtan2xtan3x=tan2x+tanx
tan3x-tan2x-tanx=tan3xtan2xtanx
AthiraUday123:
thank you
Answered by
5
Step-by-step explanation:
We know that tan 3x = tan(2x + x).
⇒ tan 3x = (tan 2x + tan x)/1 - tan 2x tan x
⇒ tan 3x(1 - tan 2x tanx) = tan 2x + tan x
⇒ tan 3x - tan 3x tan 2x tan x = tan 2x + tan x
⇒ -tan 3x tan 2x tan x = tan 2x + tan x - tan 3x
⇒ -(tan 3x tan 2x tan x) = -(tan 3x - tan 2x - tan x)
⇒ tan 3x tan 2x tan x = tan 3x - tan 2x - tan x.
∴ LHS = RHS
Hope it helps!
Similar questions